Immunohistochemistry profile and its relation with prognosis in locally advanced breast cancer - Kannanavil, Naseef; Padinjarenalakath, Nabeel Thommil; Vilayapoyilil, Ahsan; Karatparambil, Abidali (International Surgery Journal, 2019)
Background: Breast cancer is one of the most common malignancy and leading cause of cancer related deaths in women worldwide. Immunohistochemistry (IHC) is done to characterize intracellular proteins or cell-surface antigens and is used to assess tumour subtypes, confirm diagnosis, predict prognosis and response to therapy. The aim of the present study was to evaluate the relationship of IHC profile- ER, PR and HER2 neu and prognosis of patients who underwent modified radical mastectomy for locally advanced breast cancer. Methods: A retrospective cohort study was conducted at MES Medical College Hospital from October 2015 to November 2017 in patients who underwent modified radical mastectomy for locally advanced breast carcinoma. A total of 65 women were enrolled in the study. 5 years survival was taken as the prognostic indicator. Results: Majority of the patients belong to the age group of 40-49 years with 40% patients followed by 33.84% patients in the age group of 50-59 years. Maximum number of patients was found in 2B stage of tumour. Maximum patients belonged to the ER/PR+, HER2- subgroup (27), followed by triple negative (ER/PR-, HER2) subgroup (16). There was no disease related mortality in ER/PR+, HER2+ and ER/PR+, HER2- subgroups. There were 1 and 2 disease related mortality in ER/PR-, HER2+ and triple negative subgroups respectively. Conclusions: In the present study the worst prognosis was observed in triple negative (ER/PR-,HER2-) IHC subgroup followed by the HER2 enriched (ER/PR-, HER2+) subgroup.